(untitled) (GIST – Education and Learning Research Journal, 2016)
The purpose of this study was to examine ninth grade EFL students’ experiences and attitudes towards classrooms equipped with interactive whiteboards (IWB). The data were collected with a questionnaire about attitudes towards IWB use in EFL classes, and observations from three different classrooms in three different high schools. The study indicated that the EFL students were not fully aware of how to use IWBs in learning English although they had a background of IWB use. In addition, there was no statistically significant difference in the attitudes of the male and female students towards using IWBs. Overall, the results revealed that EFL students’ attitudes towards IWBs were positive although there were some technical challenges in IWB classrooms.